PENGARUH MODEL PEMBELAJARAN ROLE PLAYING TEMA PROFIL PELAJAR PANCASILA TERHADAP HASIL BELAJAR SISWA SD - Nyayu Siti Azizah; Dian Nuzulia Armariena; Noviati (STKIP Subang, 2023)
This study aims to find out and describe whether there is an influence of the role playing learning model on the Pancasila student profile theme on student learning outcomes at SD Negeri 99 Palembang. This type of research is experimental research, with a one-group pretest-posttest design. The sample of this research was 29 students of class III B. Data collection techniques using tests. The data analysis technique uses descriptive and inferential statistical analysis. The data obtained is described in words and the test results are in the form of pretest and posttest values compared to the differences between the two values. Testing the difference in values is only carried out on the average of the two values, and for this purpose the t-test technique is used. The results of this study indicate that there is an influence of the role playing learning model on the theme of the Pancasila student profile on the learning outcomes of class III students at SD Negeri 99 Palembang. This can be seen from the increase in the average value obtained by students in the learning process. The increase in student learning outcomes at the pretest averaged 51.03 increased to 77.24 on the posttest and from the t test data, the value on t_count was 10.69 while t_table with df 28 with a level of 0.05 then t_table 2.04. So it is stated that t_count 10.69 > t_table 2.04. So t_count is declared significant.